REPLACEMENT OF FISH MEAL PROTEIN BY SOY BEAN AND CORN GLUTEN MEAL PROTEINS IN THE DIET OF MUD CRAB, Scylla paramamosain - Ketut Suwirya; Nyoman Adiasmara Giri; Muhamad Marzuqi (Indonesian Aquaculture Journal, 2009)
Mud crab culture relies heavily on trash fish as the main source of feed ingredients. Artificial diets have been developed for mud crab and most of them have high content of fish meal. The increasing cost and demand of fish meal has encouraged feed manufacture to search for cheaper alternative protein sources such as plant protein. There is an urgent need to find suitable alternative protein sources to reduce the dependence of fish meal in mud crab diet. The objective of this study was to develop compounded feeds for juvenile of mud crab with reduced fish meal content, and as an alternative of trash fish feeding. For that reason, the experiment was done. Experimental diets were fish meal, 20% of soy bean (20% SBP), 40% of soy bean (40% SBP), 20% of corn gluten (20% CGP), and 40% of corn gluten meal protein (40% CGP). Average initial mud crab body weight of 0.65 ± 0.03 g was fed experimental diets for 56 days. The result showed that dietary fish meal protein can be replaced by 20% of soy bean and 20%–40% of corn gluten proteins for mud crab (Scylla paramamosain) diet. Thus, it can arguably be concluded that soy bean and corn gluten proteins are the alternative protein sources to partially replaced fish meal.